Land use change, cost-benefit of plant, and optimal crop planning in takut sub-district, muang district, Saraburi province - Thammasri, Wanpiti (Asia-Pacific Journal of Science and Technology, 2017)
This study aims to investigate land use change, cost-benefit of plant and optimal crop planning of community. The land use change and cost-benefit of plant in this research study was Takut Sub-district, Muang District, Saraburi Province. The research findings indicated that the land use change during 2010-2011 was increased from 264.75 rai to 803.25 rai. The characteristic of land use that farmers used in cultivating in-season rices, off-season rices, vegetables and fruit trees. The analysis of farmer costs in 2011 found that the average total cost of production of in-season rices, off-season rices, vegetables and fruit trees were 3,272, 3,450, 3,102, and 1,560 baht/rai, respectively. In addition, the average total benefit of production of in-season rices, off-season rices, vegetables and fruit trees were 7,390.85, 5,057.61, 3,142.14, and 1,581.80 baht/rai, respectively. The optimal crop planning in Takut Sub-district, fund that optimal crop planning of the community, farmers should product an average yield of rice 520 kg/rai, that helped the farmers to get the highest average benefit 5,558.8 baht/rai